1840 Mo. Laws 193-94 - (:unkn) unknown (My University, 1840)
An Act To Incorporate The Rural Cemetery Association, § 7.: Any person who shall willfully . . . shoot or discharge any gun or other fire arms within the said limits, shall be deemed guilty of a misdemeanor, and shall, upon conviction thereof before any justice of the peace, or any other court of competent jurisdiction within the county of St. Louis, be punished by a fine of not less than five dollars, nor more than fifty dollars, according to the nature and aggravation of the offence[.]
Keywords: DISCHARGE